1969
DOI: 10.1099/00221287-55-3-371
|View full text |Cite
|
Sign up to set email alerts
|

The Incomplete Tricarboxylic Acid Cycle in the Blue-green Alga Anabaena Variabilis

Abstract: SUMMARYThe presence of an incomplete tricarboxylic acid cycle in Anabaenu vuriabilis and Anacystis nidulans is described. These blue-green algae lack both a-oxoglutarate dehydrogenase and succinyl-CoA synthetase. Succinyl-CoA was formed in extracts of A. variabilis by 3-ketoacyl CoA-transferase using acetoacetyl-CoA as CoA donor. The activities of the other tricarboxylic cycle enzymes were measured in extracts prepared from autotrophic organisms and from those grown in the presence of acetate. No alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(72 citation statements)
references
References 10 publications
2
70
0
Order By: Relevance
“…The presence of radioactivity in glutamate, arginine and proline suggests that some aspartate had been converted to oxaloacetate which could have given rise to a-oxoglutarate and hence to glutamate, proline and arginine, The absence of a complete tricarboxylic acid cycle in A . variabilis (Pearce, Leach & Carr, 1969) prevents complete randomization of the label from aspartate into other amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of radioactivity in glutamate, arginine and proline suggests that some aspartate had been converted to oxaloacetate which could have given rise to a-oxoglutarate and hence to glutamate, proline and arginine, The absence of a complete tricarboxylic acid cycle in A . variabilis (Pearce, Leach & Carr, 1969) prevents complete randomization of the label from aspartate into other amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results have indicated that several major intermediary metabolic sequences in the blue-green algae, Anabaena variabilis and Anacystis niduluns, are not regulated by the process of repression and derepression of enzyme biosynthesis (Pearce & Carr, 1967, 1969Pearce, Leach & Carr, 1969). Blue-green algae are known to excrete large quantities of amino acids as peptides during growth.…”
Section: Introductionmentioning
confidence: 99%
“…Turnover is defined as "4CO2 released from the respective substrate. Presumably this is from carbon 1 of glucose or glucose-6-P because little or no CO2 is released by these organisms via a tricarboxylic acid cycle (12,18). Similar experiments [1-14C]glucose-6-P confirmed these results and demonstrated that the glucose-6-P turnover is primarily restricted to the activity of the pentose phosphate pathway.…”
Section: Methodsmentioning
confidence: 99%
“…Although their mode of photosynthesis seems to be essentially identical to that of eucaryotic organisms (9), a blocked tricarboxylic acid cycle and a limited glycolytic cycle, due to the absence or low levels of phosphofructokinase (11,12,16,18), suggest that carbon flow in these organisms is either by a catabolic pentose phosphate shunt, as shown by Cheung and Gibbs (5), or by direct utilization of triose produced during photosynthetic carbon reduction. The questionable functioning of glycolysis and the tricarboxylic acid cycle, and the concomitant lack of ATP synthesis in the dark, might be the reason for limited growth on glucose or acetate (11,12,16).…”
Section: Atp In Blueen Algementioning
confidence: 99%
“…Ever since the report of Smith, London & Stanier (1967) that several obligate autotrophs, blue-green algae and chemosynthetic bacteria, lacked a-ketoglutarate dehydrogenase and NADH oxidase many workers have not confirmed this evidence. Pearce & Carr (1967) noted the absence of the dehydrogenase from the blue-green alga Anabaena vulgaris, suggesting an incomplete tricarboxylic acid cycle. The incorporation of 14C actetate into only a small number of amino acids in blue-green algae (Hoare & Moore, 1965, Hoare et al 1967 and in Thiobacillus neopolitanus (Kelly, 1967) would support this view.…”
Section: Addendummentioning
confidence: 99%